Sinorhizobium meliloti RNase III: Catalytic Features and Impact on Symbiosis - Saramago, Margarida; Robledo, Marta; Matos, Rute G.; Jiménez-Zurdo, José I.; Arraiano, Cecília M. (Frontiers in Genetics, 2018)
Members of the RNase III family of enzymes are metal-dependent double-strand specific endoribonucleases. They are ubiquitously found and eukaryotic RNase III-like enzymes include Dicer and Drosha, involved in RNA processing and RNA interference. In this work, we have addressed the primary characterization of RNase III from the symbiotic nitrogen-fixing α-proteobacterium Sinorhizobium meliloti. The S. meliloti rnc gene does encode an RNase III-like protein (SmRNase III), with recognizable catalytic and double-stranded RNA (dsRNA)-binding domains that clusters in a branch with its α–proteobacterial counterparts. Purified SmRNase III dimerizes, is active at neutral to alkaline pH and behaves as a strict metal cofactor-dependent double-strand endoribonuclease, with catalytic features distinguishable from those of the prototypical member of the family, the E. coli orthologue (EcRNase III). SmRNase III prefers Mn2+ rather than Mg2+ as metal cofactor, cleaves the generic structured R1.1 substrate at a site atypical for RNase III cleavage, and requires higher cofactor concentrations and longer dsRNA substrates than EcRNase III for optimal activity. Furthermore, the ultraconserved E125 amino acid was shown to play a major role in the metal-dependent catalysis of SmRNase III. SmRNase III degrades endogenous RNA substrates of diverse biogenesis with different efficiency, and is involved in the maturation of the 23S rRNA. SmRNase III loss-of-function neither compromises viability nor alters morphology of S. meliloti cells, but influences growth, nodulation kinetics, the onset of nitrogen fixation and the overall symbiotic efficiency of this bacterium on the roots of its legume host, alfalfa, which ultimately affects plant growth. Our results support an impact of SmRNase III on nodulation and symbiotic nitrogen fixation in plants.